Síntomas depresivos y trastorno motor en pacientes con enfermedad de Parkinson - Stella, Florindo [UNESP]; Bucken-Gobbi, L. T. [UNESP]; Gobbi, S. [UNESP]; Sant'Ana-Simões, C. [UNESP] (My University, 2007)
Introduction. Complex relations between brain and psychopathology have attracted the interest of researchers, aiming to clarify the neurobiological mechanisms of depression in Parkinson's disease, obviously in addiction to mental features. Aims. The association of motor impairment and decline of personal autonomy with severity of depressive symptoms was the hypothesis of the present study. Aiming to check this hypothesis, the objective of this study consisted in investigating relationships between the severity of depressive symptoms and motor characteristics of Parkinson's disease. Patients and methods. Thirty patients (53 to 80 year-old) with medical diagnosis of idiopathic Parkinson's disease in initial clinic stages were studied. The Unified Parkinson's Disease Rating Scale, Hoehn-Yahr Scale, and Schwab & England Scale were used to assess the clinic signs and symptoms. The depressive symptoms were identified by complete anamnesis, examination of mental condition, and the Hamilton Rating Scale for Depression and the Anxiety and Depression Scale. Statistical analysis was performed by Pearson's correlation and multiple regression analysis. Results. A significant correlation of severity of depression symptoms with disease stage (p < 0.02), with motor signs (p < 0.008), and with functional performance (p < 0.007) was found. Conclusion. There was significant association between motor impairment and severity of depressive symptoms, and between depression and early disease onset or prolonged duration of Parkinson's disease. © 2007, Revista de Neurología.
Depressive symptoms and motor condition in Parkinson's disease patients
Keywords: Daily living activities; Depressive symptoms; Motor signs; Movement disorders; Parkinson's disease; Personal autonomy; adult; aged; anamnesis; Anxiety and Depression Scale; clinical article; clinical assessment; clinical feature; correlation coefficient; daily life activity; depression; disease association; disease severity; female; Hamilton scale; Hoehn Yahr Scale; human; hypothesis; male; mental health; motor dysfunction; multiple regression; named inventories, questionnaires and rating scales; Parkinson disease; schwab and england scale; statistical analysis; statistical significance; Unified Parkinson Disease Rating Scale; Activities of Daily Living; Aged; Aged, 80 and over; Antiparkinson Agents; Depression; Female; Humans; Male; Middle Aged; Motor Activity; Parkinson Disease; Psychiatric Status Rating Scales; Quality of Life; Sickness Impact Profile; Statistics as Topic